Megah Enterprise : heavy vehicle rental service / Faizal Mustafa ... [et al.] - Mustafa, Faizal; Yasin, Mohd Hafizun; Mohd Adam, Mat Radzi; Ismail, Mohd Hafiszul (2002)
Megah Enterprise is operating on heavy vehicle rental service and insfrastructure supplier. This company is situated at Kubang Gajah Arau, Perlis.